Tungsten-Catalyzed Allylation of Sulfonyl Hydrazides: Regioselective Synthesis of Branched Allylic Sulfones - Xu, Wenbin (Synlett, 2025)
A highly regioselective tungsten (W)-catalyzed allylic sulfonylation of allylic carbonates with readily available sulfonyl hydrazides has been developed. Under tungsten catalysis, a variety of allylic sulfones can be delivered with the help of 4,4′-di-tert-butyl-2,2′-bipyridine in moderate to good yields with excellent b/l regioselectivities. This approach features mild conditions, broad substrate scope, where aryl- and alkyl-substituted allylic carbonates and sulfonyl hydrazides are suitable substrates. This noble-metal-free catalyst system exhibits high reactivity and regioselectivity for the construction of C–S bond.
Keywords: Allylic substitution; Noble-metal-free catalysis; Tungsten; C–S formation; Sulfone